Five years of multi-depot vehicle routing problems - Jayarathna, N.; Lanel, J.; Juman, Z.A.M.S. (Journal of Sustainable Development of Transport and Logistics, 2020)
With vast range of applications in real life situations, the Vehicle Routing Problems (VRPs) have been the subject of countless studies since the late 1950s. However, a more realistic version of the classical VRP, where the distribution of goods is done from several depots is the Multi-Depot Vehicle Routing Problem (MDVRP), which has been the central attraction of recent researches. The objective of this problem is to find the routes for vehicles to serve all the customers at a minimal cost in terms of the number of routes and the total distance travelled without violating the capacity and travel time constraints of the vehicles, and it is handled with a variety of assumptions and constraints in the existing literature. This survey reviews the current status of the MDVRP and discuss the future direction regarding this problem.
Keywords: multi-depot vehicle routing problem, exact methods, heuristic, meta-heuristic.